Dinâmica do processo decisional e fluxo adaptativo de sistemas de produção leiteiros de base familiar - Bodenmüller Filho, Anselmo (2011)
This work of exploratory nature and systemic approach, seeks to collaborate in the development of research criteria and techniques on dairy production systems (DPS). The main objective is to study how the DPS incorporate technology. For the development of the study, interviews based on a questionnaire were conducted in 60 properties, starting from the dairy region of the southwestern region of Paraná. In the first study, the database allowed showing the profiles of dimensioning from the areas planted with forage and their respective proportions and relations, together with indicative of productive results. The groups portray the dynamic of the management of forage resources and mark the diversity of managers' objectives, setting five dimensioning logics of the forage area to meet the demand. The second study was conducted with the objective of evaluating the decision-making profiles focusing on the dynamics of information flows, social interactions, biographical features and administrative management using multivariate analysis techniques. According to an appropriate approach to decision making and technical advice the preferential practices of searching for technical information were highlighted, considering the mechanisms of knowledge dissemination triggered to transfer technology. Important variables were identified based on biographical and management indicators which define the factors for DPS modeling. The third study was carried out with the purpose of verifying that the study of practices in management positions contributes to explain the diversity of DPS. And it also allows to list the implications of this approach on the decision-making process in family farming. We tried to outline the general strategies used in the studied DPS by the interpretation of factorial axes using the multiple correspondence analysis (MCA). The study showed that there is DSP diversity in the region studied with unevenly allocated logics for the construction of the results. The results provide support for the studies on technology diffusion in order to promote increased rate of adoption of new practices with an impact on agricultural development.